Serological screening of Peste des petits ruminants, comparative haemodynamic changes and serum biochemical profiles in symptomatic and asymptomatic sheep and goats in Enugu State - Chukwudi, I.C.; Ogbu, K.I.; Ugwu, G.N.; Ugochukwu, E.I.; Chah, K.F. (Nigerian Journal of Animal Science, 2023)
Haemo-biochemical profile of small ruminants (SR) within age range 12-18 months exhibiting clinical signs suggestive of Peste des petits ruminants (PPR) (n=80) and apparently healthy ones (n=20) was studied. Blood samples (5 ml) were collected from the SR displaying a combination of the following clinical signs: nasal and ocular discharges, cough, diarrhoea, respiratory distress, weakness and emaciation, and from the apparently healthy ones. Sera and whole blood were analysed for the presence of PPRV antibodies using competitive ELISA kit as a screening test and haemo-biochemical profile using standard techniques respectively. Out of the 80 SR exhibiting clinical signs suggestive of PPR, sera from 51 (63.8%) were positive for the PPRV antibody and all of the apparently healthy ones were PPRV seronegative. There was a significant association (p<0.05) between those displaying clinical signs and seropositivity. The mean white blood cell of PPRV positive sheep and goats were significantly lower (p<0.05) than apparently healthy sheep and goats. Significant differences (p<0.05) in the packed cell volume (PCV), red blood cell (RBC) and platelet counts were observed in PPRV positive goats when compared with apparently healthy goats. The aspartate transaminase, alanine aminotransferase, total protein, albumin, urea, creatinine and potassium of PPRV positive sheep and goats differ significantly (p<0.05) from the apparently healthy sheep and goats. PPRV positive goats had significant higher (p<0.05) total bilirubin and significant lower (p<0.05) sodium level than the apparently healthy goats. Antidiarrheal agents with aqua solution together with immuno-modulators could help improve the management of PPR infection in SR.